Den ’rigtige’ sex - Moralsk orientering,seksualmoralisme og (hetero)normativitet i midt- og sen-00’ernes seksualdebat i Danmark - Wøldike, Morten Emmerik (Slagmark - Tidsskrift for idéhistorie, 2018)
The article presents and discusses a critical textual analysis of opinions and attitudes towards various sexual phenomena articulated in the Danish print media during 2004-2006 compared with 1997. The study proves that sexual pleasures and practices such as anal sex, group sex, pornography, sexualisation and prostitution have given rise to increasing moral anxieties and fears, condemnatory attitudes and moralistic standpoints during the last few years. These moralistic and normative standpoints on sexual morality put forward clear specifications as to how people should live their lives and what sexual and bodily pleasures and practices they should be allowed to enjoy. Drawing inspiration from the writings of French philosopher Michel Foucault on ‘ethics’ and ‘aesthetics of existence’, the article suggests an ethical approach and sensibility when dealing morally with people’s sexual and bodily pleasures and practices as well as when doing research on sexual phenomena such as anal sex, pornography and commercial sex.